Private cities and consumption: urban development patterns in Southeast Asia / Surya Gunanta Tarigan - Gunanta Tarigan, Surya (Universiti Teknologi MARA, Perak, 2022)
The strengthening of international capital in urban development has made many cities compete to attract global investors. To achieve that, many Southeast Asian governments implement policies that emphasise foreign direct investment to help the poor performance of the local states in the delivery of urban collective goods. Local and international private developers invest in large-scale townships to fulfil housing and investment demand. The creation of office centres, commercial hubs, and middle-class housing estates with international standards is encouraged to accommodate the needs of foreign capital and increase urban competitiveness. Moreover, as part of the new township development, shopping malls and convenience stores promote global consumption through global franchises, chain stores, and name-brand merchandise. Private city development indicates that these projects have become powerful forces in shaping the ongoing urban transition in many countries. The study explores the phenomena from literature review and focus group discussion with private developers, academicians, governments, and non-government organisations in Indonesia as the case study. The study shows that the role of the private sector has become more critical than ever. The private sector can also maximise its influence by building a modern city image and integrating global franchises into their area of development.